Evaluation to Improve a High School Summer Science Outreach Program - Katherine B. Chiappinelli (American Society for Microbiology, 2016)
The goal of the Young Scientist Program (YSP) at Washington University School of Medicine in St. Louis (WUSM) is to broaden science literacy and recruit talent for the scientific future. In particular, YSP seeks to expose underrepresented minority high school students from St. Louis public schools (SLPS) to a wide variety of careers in the sciences. The centerpiece of YSP, the Summer Focus Program (SFP), is a nine-week, intensive research experience for competitively chosen rising high school seniors (Scholars). Scholars are paired with volunteer graduate student, medical student, or postdoctoral fellow mentors who are active members of the practicing scientific community and serve as guides and exemplars of scientific careers. The SFP seeks to increase the number of underrepresented minority students pursuing STEM undergraduate degrees by making the Scholars more comfortable with science and science literacy. The data presented here provide results of the objective, quick, and simple methods developed by YSP to assess the efficacy of the SFP from 2006 to 2013. We demonstrate that the SFP successfully used formative evaluation to continuously improve the various activities within the SFP over the course of several years and in turn enhance student experiences within the SFP. Additionally we show that the SFP effectively broadened confidence in science literacy among participating high school students and successfully graduated a high percentage of students who went on to pursue science, technology, engineering, and mathematics (STEM) majors at the undergraduate level.